The influence of leader-subordinate emotional intelligence congruence on the flow experience: evidence from the liquor manufacturing industry - Lu, Zhuoran (Frontiers in Psychology, 2024)
Previous research has provided evidence supporting a positive correlation between emotional intelligence (EI) and flow. However, intriguing findings in the liquor manufacturing industry prompt me to consider the necessity of examining the effects of leader-subordinate EI congruence on flow.Therefore, this article begins with two questions: First, what is the impact of leader-subordinate EI congruence on flow? Second, do two distinct congruent scenarios (i.e., high-high and low-low) exhibit significant nuances that differentially influence flow? To answer these questions, this study utilizes polynomial regression and three-dimensional response surface analysis methods. A multisource and three-phase investigation method was used to collect data from 279 subordinates and 56 leaders in the liquor manufacturing industry. Based on the person-environment (PE) fit theory, this study investigates the influence of leader-subordinate EI congruence on flow while considering leader-member exchange (LMX) as a mediator in these processes. The current study not only demonstrates a positive relationship between leader-subordinate EI congruence and LMX, but also reveals that a high-high EI matching pattern can enhance the favorable dynamics of congruence and yield higher LMX compared to a low-low matching pattern. Furthermore,this study identifies LMX as a mediator in the positive relationship between leader-subordinate EI congruence and flow.Additionally, although the incongruent scenarios are beyond the scope of this study, the findings demonstrate that a high EI subordinate paired with a low EI leader has a more detrimental impact on the LMX than a low EI subordinate paired with a high EI leader. Theoretical and practical implications are discussed.